PENGARUH PROMOSI, LOKASI, DAN KUALITAS LAYANAN TERHADAP LOYALITAS PELANGGAN - Norrahma, Norrahma; Sulistyowati, Pemilia (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
This study aims to determine and analyze the direct effect of promotion on customer loyalty at PT. Bintang Tsajaja Jambi, to determine and analyze the direct effect of location on customer loyalty at PT. Bintang Tsajaja Jambi, to determine and analyze the direct effect of service quality on customer loyalty at PT. Bintang Tsajaja Jambi and to determine and analyze the simultaneous effect of promotion, location, service quality on customer loyalty at PT. Bintang Tsajaja Jambi. This study uses a quantitative method with a sample of 70 customer respondents at PT. Bintang Tsajaja Jambi. Data were analyzed using validity tests, reliability tests, multicollinearity tests, heteroscedasticity tests, normality tests, multiple linear regression analysis tests, T tests, F tests, R2 determination coefficient tests using IBM SPSS Statistics. The results showed that promotion directly had a significant effect on customer loyalty at PT. Bintang Tsajaja Jambi, service quality directly had a significant effect on customer loyalty at PT. Bintang Tsajaja Jambi, location directly had a significant effect on customer loyalty at PT. Bintang Tsajaja Jambi, and directly and simultaneously promotion, location, and service quality have a significant effect on customer loyalty to customers at PT. Bintang Tsajaja Jambi.